(untitled) - Pearce, Jean (New York,Tokyo, 1976)
A long-time Tokyo resident takes readers on a walking tour around each station along the Yamanote Line that circles the heart of Tokyo, offering glimpses of the variety in this city that at first glance seems homogenous.
Keywords: Yamatesen